Emergence of non-motor fluctuations with reference to motor fluctuations in Parkinson's disease. (September 2018) - Kim, Aryun; Kim, Han-Joon; Shin, Chae Won; Kim, Ahro; Kim, Yoon; Jang, Mihee; Jung, Yu Jin; Lee, Woong-Woo; Park, Hyeyoung; Jeon, Beomseok
Abstract: Introduction: Non-motor fluctuations (NMF) and motor fluctuations (MF) are frequent in patients with Parkinson's disease (PD) with long-term medical treatment. We aimed to examine the timing of the emergence of NMF with reference to MF in a prospective cohort of patients with PD without symptom fluctuations. Methods: A total of 334 patients with PD who had neither MF nor NMF were recruited. The exclusion criteria included a Mini-Mental State Examination score of less than 26 points at baseline and an alternative diagnosis or significant comorbidity during follow-up. The "SNUH-Fluctuation Questionnaire" consisting of 29 items (9 on MF and 20 on NMF) was administered on a semi-annually basis for 3 years. Results: Three hundred seven out of 334 patients were analyzed for symptom fluctuations with the Kaplan-Meier survival analysis. MF were observed in more patients and developed earlier than NMF (cumulative survival of 0.572 for MF and 0.619 for NMF at 36 months of follow-up). In 212 patients who finished the follow-up for 36 months, MF and NMF developed simultaneously in 58 (27.4%), MF developed first in 45 (21.2%), and NMF developed first in only 3 (1.4%). The remaining 106 patients (50.0%) did not develop either MF or NMF. Conclusion: NMF developed simultaneously with or later than MF. From these data, we hypothesize that NMF develop in the disease state where the pathology in the brain has been severe enough to develop MF. Hence, pharmacologic management should consider targeting both dopaminergic and non-dopaminergic systems to treat NMF. Highlights: Half of the patients with early PD developed symptom fluctuations after 5 years from disease onset. Most fluctuators developed MF and NMF simultaneously (55%) or MF first (43%). Almost all the patients with NMF also developed MF. NMF usually develop when the disease status is severe enough to develop MF.